The Translator’s Predicament: A View of Linguistic, Cultural and Contextual Problems - Sheliyna, S. (My University, 2021)
A definition of translation cannot very easily be given. If we were to look the word up in a dictionary (Webster’s Dictionary) we would see that translating means changing spoken or written words into another language. The translation activity is very old. It has been generated by the existence of more than one language on this planet and will continue to exist unless humankind came up with a unique language to communicate in. People who have never translated often assume that it is a purely mechanical process. The translator, proficient in both languages, simply has to substitute one word in the source language for an equivalent word in the target language. To some extent this is true, particularly for texts with specific and frequently repeated terminology such as machine manuals, and especially if those texts are being translated into a language related to one’s own. There are several problems faced by the translator at linguistic level such as at phonology, morphology, syntax, and semantics, cultural level-such as at idioms, proverbs, greetings etc., and contextual level for instance at Metonymy. Each and every problem of translation should be overcome in order to produce an effective translation. Therefore, the present paper aims at a view of Linguistic, Cultural and Contextual problems in the Art of Translation and at overcoming those problems using appropriate techniques and strategies.
Keywords: Translation; Predicament; Problems; Techniques; Strategies